The The elusive time in schools: students of the Mexico state during the mid-nineteenth century (2020)
What is it possible to know about the daily activities of schoolchildren from the mid-19th century? To what extend knowing their daily activities can serve to understand aspects of Hispanic American society? The work recovers experiences lived in educational areas of the Toluca Valle in the State of Mexico in the mid-nineteenth century, paying attention to students’ activities. There is a point of intersection between the history of education and childhood. The analysis will characterize patterns linked to their assistance, daily experiences, and punishments. With a qualitative analysis, testimonies from different files are collected, in which the privilege of the perspective is noticed from sources recovered in municipal historical repositories. From them it has been possible to attend to specificities that could hardly have been recognized from a more general perspective. The purpose is to carry out a social and cultural history of education in which students are the focus of attention. What was analyzed focuses on the Toluca region, but the perspective suggests that the elusive visibility of these students responds to aspects of society in this period.